Organizational environment and governance structures of intermunicipal consortia for food security : brazilian cases - Chaebo, Gemael (2013)
The objective of this paper is describe the organizational environment and governance structures in Consortia for Food Security and Local Development (Consad) located in geographical regions of the state of Mato Grosso do Sul. The multiple-case study on which the paper is based was qualitative and descriptive in nature. Semi-structured interviews (133) were conducted in organizations located in these regions having Consads and analyzed using content analysis technique. Results reveal the existence of organizations oriented toward providing support to rural/agricultural undertakings. Although formal partnership agreements exist, both organizations participating in Consads and those not participating evinced lack of knowledge about the objectives and projects of Consad. In terms of governance, it proved not possible to identify any sort of coordinating agent for local Consad initiatives. The study contributes to understanding the organizational dynamics involved in the food security consortia in Brazil.